2016
DOI: 10.1038/srep24161
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle Myosin IIA Regulates Intestinal Epithelial Barrier in vivo and Plays a Protective Role During Experimental Colitis

Abstract: The actin cytoskeleton is a critical regulator of intestinal mucosal barrier permeability, and the integrity of epithelial adherens junctions (AJ) and tight junctions (TJ). Non muscle myosin II (NM II) is a key cytoskeletal motor that controls actin filament architecture and dynamics. While NM II has been implicated in the regulation of epithelial junctions in vitro, little is known about its roles in the intestinal mucosa in vivo. In this study, we generated a mouse model with an intestinal epithelial-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 54 publications
4
65
0
Order By: Relevance
“…Some investigators have argued that, because MLCK could, theoretically, phosphorylate substrates other than myosin II regulatory light chain, a more appropriate study would be to analyze mice lacking nonmuscle myosin IIA heavy chain specifically within the intestinal epithelium (Naydenov et al 2016). However, these tissue-specific nonmuscle myosin IIA heavy chain-deficient mice display barrier defects and intestinal disease under basal (i.e., unstressed) conditions.…”
Section: Tumor Necrosis Factor-mediated Regulation Of Tight Junction mentioning
confidence: 99%
“…Some investigators have argued that, because MLCK could, theoretically, phosphorylate substrates other than myosin II regulatory light chain, a more appropriate study would be to analyze mice lacking nonmuscle myosin IIA heavy chain specifically within the intestinal epithelium (Naydenov et al 2016). However, these tissue-specific nonmuscle myosin IIA heavy chain-deficient mice display barrier defects and intestinal disease under basal (i.e., unstressed) conditions.…”
Section: Tumor Necrosis Factor-mediated Regulation Of Tight Junction mentioning
confidence: 99%
“…98 Both inhibition and activation of NM II disrupts the epithelial barrier and triggers AJ and TJ disassembly. 99101 Likewise, recent studies using knockout and transgenic mouse models revealed that both the inhibition of the actin motor, via the intestinal epithelial-specific knockout of NM IIA, 102 and overactivation of NM II, via the overexpression of constitutively active MLCK in the intestinal epithelium, 103 resulted in increased intestinal permeability. These findings suggest that balanced NM II activity controls integrity of the gut barrier.…”
Section: Intercellular Junctionsmentioning
confidence: 99%
“…Pathogenic Escherichia coli can target Gp96 to promote nitric oxide production, Ca 2+ oscillations and activation of cellular kinases such as PKC-a and FAK, which disrupts endothelial cell junctions and mediates bacterial internalization [40]. LLO and other PFTs trigger such events, which were associated with increased tissue damage in vivo [41,42], and NMHCIIA protects the epithelial barrier in vivo [43]. Interestingly, Lm can interact with Gp96 via its surface protein Vip, which promotes bacterial internalization [18].…”
Section: Embo Reportsmentioning
confidence: 99%